Sosialisasi Pemanfaatan Google Sites Sebagai Personal Web Di SMK Bistek Cibinong - Badriah Nursakinah; Andin Eka Safitri; Octaviana Anugrah Ade Purnama (CV. Multi Kreasi Media, 2022)
Abstract− In the era of globalization where Teknologi, informasi, and Komunikasi is growing very quickly, the world of education is experiencing changes in its management as a result of the demands of utilizing technology.. Changes in learning and demands for innovation are important things that must be done. Various applications are available and can be used by teachers to develop learning media. The website was originally developed as hypertext where documents are presented electronically that are integrated with each other. Hypertext not only presents text, but can store images, sound and video to develop into multimedia, Websites which are actually the World Wide Web are very important and are most often used in the internet world. Website is an application that is very fast growing and the most widely used. From the information system that is in great demand from an agency or institution is a website which is a facility that displays and searches for information. And the use of the use of the google sites itself in addition to adding insight about the use of google sites intelligently. Based on the socialization analysis of the results of the service carried out, it can be concluded that the benefits of google sites help facilitate website creation, because there is no need for expert expertise to code.